Pemberdayaan Kelompok Sadar Wisata (Pokdarwis) Tiram Tambun dalam Mengembangkan Desa Wisata Mentawir Kabupaten Panajam Paser Utara - Yogiana Mulyani; Saiful Ghozi; Henry Winnarko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Abstract Mentawir Tourism Village is a tourism village located in Penajam Paser Utara, East Kalimantan. This Tourism Village has “Pokdarwis” (Tourism Awarness Group) which has been formally confirmed by the head Department of Culture and Tourism in Penajam Paser Utara on August 7, 2019. However, the development of the Mentawir Tourism Village has not been maximized so it is necessary to empower more of the Pokdarwis Tiram Tambun to strengthen the management and promotion of the Mentawir Tourism Village. Several problems occurred in the Mentawir Tourism Village such as the lack of ability to manage the Pokdarwis Tiram Tambun institutions that were ineffective, inefficient and intransparent. They are also incapable to promote through various media and product of breakfast menu in their own homestay. The approachment methods used in this activities including socialization, training and mentoring. The results of these activities including the knowledge and skills of the management and members of the Pokdarwis Tiram Tambun to increase or to improve in terms of effective, efficient and transparent management through improving the administration or organizational bookkeeping, the development of potential tourism in the Mentawir village can be mapped through tourism products in the form of tour packages that will be offered to the tourists, as well as increasing the promotion of the Mentawir itself through various social media in order to increase the number of tourists visiting there and improvement skill from homestay owners in producing breakfast dishes Abstrak Kelurahan Mentawir merupakan Kawasan berpotensi wisata yang terletak di Kecamatan Sepaku, Kabupaten Penajam Paser Utara, Kalimantan Timur. Potensi wisata didaerah ini dikelola oleh Kelompok Sadar Wisata (Pokdarwis) Tiram Tambun yang telah mendapatkan pengukuhan secara resmi oleh Kepala Dinas Kebudayaan dan Pariwisata Kabupaten Panajam Paser Utara pada tanggal 7 Agustus 2019. Namun dalam pengembangan Wisata Mentawir belum maksimal sehingga perlu dilakukan pemberdayaan Pokdarwis untuk memperkuat pengelolaan dan promosi Desa Wisata Mentawir. Beberapa permasalahan di Wisata Mentawir antara lain kurangnya kemampuan dalam mengelola kelembagaan Pokdarwis yang efektif, efisien dan transparan, kurangnya kemampuan dalam melakukan promosi melalui berbagai media, serta kurangnya ketrampilan dalam pengolahan menu makan pagi di homestay. Metode pendekatan yang dilakukan dalam kegiatan ini antara lain sosialisasi, pelatihan dan pendampingan. Hasil dari kegiatan memberikan dampak bertambahnya pengetahuan dan keterampilan pengurus dan anggota Pokdarwir Tiram Tambun yang efektif, efesien dan transparan. Kegiatan pendampingan ini juga menghasilkan pemetaan paket-paket wisata yang akan ditawarkan kepada wisatawan. Selain itu, hasil yang dicapai dibidang pemasaran digital adalah meningkatnya atau bertambahnya promosi desa wisata Mentawir melalui berbagai media sosial dalam rangka mensosialisasikan potensi Mentawir kepada wisatawan, serta bertambahnya ketrampilan dari pengelolaan dan pelayanan di homestay.